Accumulation of Carotenoids and Expression of Carotenoid Biosynthetic Genes during Maturation in Citrus Fruit - Kato, Masaya (The American Society for Plant Biologists, 2004)
The relationship between carotenoid accumulation and the expression of carotenoid biosynthetic genes during fruit maturation was investigated in three citrus varieties, Satsuma mandarin (Citrus unshiu Marc.), Valencia orange (Citrus sinensis Osbeck), and Lisbon lemon (Citrus limon Burm.f.). We cloned the cDNAs for phytoene synthase (CitPSY), phytoene desaturase (CitPDS), ζ-carotene (car) desaturase (CitZDS), carotenoid isomerase (CitCRTISO), lycopene β-cyclase (CitLCYb), β-ring hydroxylase (CitHYb), zeaxanthin (zea) epoxidase (CitZEP), and lycopene ε-cyclase (CitLCYe) from Satsuma mandarin, which shared high identities in nucleotide sequences with Valencia orange, Lisbon lemon, and other plant species. With the transition of peel color from green to orange, the change from β,ε-carotenoid (α-car and lutein) accumulation to β,β-carotenoid (β-car, β-cryptoxanthin, zea, and violaxanthin) accumulation was observed in the flavedos of Satsuma mandarin and Valencia orange, accompanying the disappearance of CitLCYe transcripts and the increase in CitLCYb transcripts. Even in green fruit, high levels of β,ε-carotenoids and CitLCYe transcripts were not observed in the juice sacs. As fruit maturation progressed in Satsuma mandarin and Valencia orange, a simultaneous increase in the expression of genes (CitPSY, CitPDS, CitZDS, CitLCYb, CitHYb, and CitZEP) led to massive β,β-xanthophyll (β-cryptoxanthin, zea, and violaxanthin) accumulation in both the flavedo and juice sacs. The gene expression of CitCRTISO was kept low or decreased in the flavedo during massive β,β-xanthophyll accumulation. In the flavedo of Lisbon lemon and Satsuma mandarin, massive accumulation of phytoene was observed with a decrease in the transcript level for CitPDS. Thus, the carotenoid accumulation during citrus fruit maturation was highly regulated by the coordination of the expression among carotenoid biosynthetic genes. In this paper, the mechanism leading to diversity in β,β-xanthophyll compositions between Satsuma mandarin and Valencia orange was also discussed on the basis of the substrate specificity of β-ring hydroxylase and the balance of expression between upstream synthesis genes (CitPSY, CitPDS, CitZDS, and CitLCYb) and downstream synthesis genes (CitHYb and CitZEP).